10 years of frontiers in carbon-based materials: carbon, the “newest and oldest” material. The story so far - Flores-Lasluisa, Jhony Xavier; Navlani-García, Miriam; Berenguer-Murcia, Ángel; Morallón, Emilia; Cazorla-Amorós, Diego (Frontiers in Materials, 2024)
While carbon in itself appears as simple an element as it could possibly get, the undeniable truth is that carbon materials represent a plethora of possibilities both from the perspective of their structure and their applications. While we may believe that carbon is “just another element”, one should never forget that its special ability to coordinate through different hybridizations with apparent ease grants the element properties that no other element may even match. Taking this one step further into the materials realm opens up numerous avenues in terms of materials dimensionality, surface and bulk functionalization, or degree of structural order just to mention a few examples. If these properties are translated into the properties and applications field, the results are just as impressive, with new applications and variants appearing with growingly larger frequency. This has resulted in over a million scientific papers published in the last decade in which the term “carbon” was used either in the title, abstract or keywords. When the search is narrowed down to the field “title” alone, the results drop to just over 318.000 scientific papers. These are figures that no other element in the periodic table can equal, which is a clear indicative that the story of carbon materials is still under constant evolution and development. This review will present an overview of the works published in the Frontiers in Carbon-based materials section during its ten years of life that reflect the advancements achieved during the last decade in the field of carbon materials.